1998
DOI: 10.1016/s0735-1097(98)00386-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of three-dimensional echocardiography during balloon mitral valvuloplasty

Abstract: The three-dimensional echocardiographic reconstruction enabled visualization of the mitral valve so that commissural splitting and leaflet tears not seen on the two-dimensional echocardiogram became visible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Furthermore, it has also been reported that 3D may provide a better visualization of tear that can occur during PMC. 8 Thus RT3DE may guide and optimize PMC results by visualizing, during the procedure, the extent of commissural splitting so that maximal MVA can be achieved safely.…”
Section: Assessment Of Commissural Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has also been reported that 3D may provide a better visualization of tear that can occur during PMC. 8 Thus RT3DE may guide and optimize PMC results by visualizing, during the procedure, the extent of commissural splitting so that maximal MVA can be achieved safely.…”
Section: Assessment Of Commissural Openingmentioning
confidence: 99%
“…The 3D shape of the mitral valve orifice is complex and preliminary data suggest that 3DE could visualize commissural splitting more accurately than 2DE. [8][9][10] In these series, a transoesophageal probe interfaced with a workstation was used. Clinical use of RT3DE (transthoracic imaging) for the assessment of the degree of commissural splitting has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved, that 3DE is better in the morphological assessment of the mechanism of mitral balloon valvuloplasty in comparison with 2DE [28]. Surface rendered 3DE images enable visualization of commissural splitting and leaflet tears not seen on 2DE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 3D TEE provides superior anatomic imaging of commissural calcification and fusion (Video 2), which is particularly important in patients undergoing PMBC, as well as detection of post-intervention commissural splitting and leaflet tears [75,77,78].…”
Section: Transesophageal Echocardiographymentioning
confidence: 99%